2021
DOI: 10.1016/j.cmi.2021.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac sequelae after coronavirus disease 2019 recovery: a systematic review

Abstract: Background Coronavirus disease 2019 (COVID-19) has been implicated in a wide spectrum of cardiac manifestations following the acute phase of the disease. Objectives To assess the range of cardiac sequelae after COVID-19 recovery. Data sources PubMed, Embase, Scopus (inception through 17 February 2021), and Google scholar (2019 through 17 February 2021). Study eligibility criteria Prospective and retrospective studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 74 publications
2
68
2
5
Order By: Relevance
“…Symptom burden appears to be independent of the severity of initial infection, with no clear predictors of who will develop ongoing symptoms [10]. Persistent endothelial dysfunction may be responsible for the wide variation in symptoms reported [11][12][13]. There is also some evidence suggesting that altered inflammatory cytokine pathways may persist during convalescence [14].…”
Section: Introductionmentioning
confidence: 99%
“…Symptom burden appears to be independent of the severity of initial infection, with no clear predictors of who will develop ongoing symptoms [10]. Persistent endothelial dysfunction may be responsible for the wide variation in symptoms reported [11][12][13]. There is also some evidence suggesting that altered inflammatory cytokine pathways may persist during convalescence [14].…”
Section: Introductionmentioning
confidence: 99%
“…A myocarditis-pattern was observed up to 30 days after SARS-CoV-2 infection in the 27% of 148 patients in the UK who had myocardial injury [ 11 ]. Data on pericardial involvement are scarce, and a recent systematic literature review (SLR) including studies on adult patients undergoing any type of cardiac assessment after COVID-19 recovery reported a prevalence of pericardial enhancement in 63/758 patients and of pericardial effusion in 99/758 patients (on cardiac magnetic resonance (CMR)) or 12/811 patients (on echocardiography) [ 12 ]. Unfortunately, only four studies on CMR included in the SLR reported a formal clinical diagnosis of myopericarditis (15/785 patients) and pericarditis (4/785 patients), while only one study using echocardiography reported a formal clinical diagnosis of pericarditis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular manifestations in the post-acute phase of COVID-19 described in the studies so far have ranged from asymptomatic changes in CMR exploration to symptoms of heart failure, including palpitations, tightness, dizziness, and chest pain. The frequency of them varied greatly between different reports [95][96][97]. Most of these studies were observational and without a control arm in some cases.…”
Section: Long Covid and Post-acute Covid-19 Syndromementioning
confidence: 99%
“…However, there are still many questions regarding the pathophysiologic mechanisms and the real implications of imaging findings of the acute and post-acute phase on the longterm prognosis. Studies suggested that patients who have recovered from COVID-19 will present a greater risk for a range of cardiac diseases, including heart failure, myocardial infarction (MI), and arrhythmia in the mid-and long-term [95].…”
Section: Chronic Effects Of Covid-19 On the Cardiovascular System: Evidence At Mid-and Long-term Follow-upmentioning
confidence: 99%